Cyber Language used by University Students: Textual Analysis of Facebook page “Confessions” - Arias Chávez, Dennis (2018)
The presentation of the cyber language as one of the variations of the language includes a discussion on its nature as an intermediate form between oral language and written language and the forces responsible for the linguistic changes. On the one hand, we have the popular usage that has given rise to the constant evolution of the language and, on the other hand, the educated speech which strives to recover its etymological form (Betancourt, 2010). The objective of the present study is to analyze the linguistic phenomena present in the texts listed on the Facebook page called “Confessions” of 6 Peruvian universities, 3 from the city of Arequipa and 3 subsidiaries of Lima universities in this city. The corpus consists of 70 texts, the design is transversal, descriptive and documentary and we used as a tool a registration form of linguistic variations in which spelling, lexical-semantic and lexicalsyntactic features were collected and analyzed, in addition to the function of the language used in this means. The study demonstrates the existence of a different variety of distinctly creative texts. Regarding the spelling features, we found the vowel elision, substitution and multiplication of consonant graphemes. Lexical-semantic features of the analyzed texts show a marked use of euphemisms, colloquial words and anglicisms. From the lexical-syntactical point of view, the analysis shows that despite the more or less informal nature of the means used (Facebook), the messages that are transmitted are texts which develop comprehensive and complex argumentations. Finally, functions that are prevalent in the texts are the emotional and phatic ones.